ANALISIS PEMILIHAN DAN PRODUKTIVITAS ALAT BERAT PADA PEKERJAAN JASA ANGKUT PADA PROYEK BATU BARA DISITE STG (STEAM TURBINE GENERATOR) PT PUPUK SRIWIDJAJA PALEMBANG - Ramadan, Virgia Renzi; Rosyad, Farlin (Ensiklopedia of Journal, 2024)
This study aims to analyze the selection and productivity of heavy equipment in coal hauling services. The analysis method is carried out by evaluating various types of heavy equipment used, including excavators, trucks, and bulldozers, as well as factors that affect their efficiency. Data were collected through field observations and interviews with operators. The results of the study indicate that the selection of the right heavy equipment can increase productivity and reduce operational costs. These findings are expected to provide guidance for coal hauling service companies in selecting optimal equipment to improve project performance and profitability.Keywords: heavy equipment selection, productivity, coal transportation services, efficiency, operational costs.